Engineering coercivity in YFe2 dominated DyFe2/YFe2 superlattice by patterning - Wang, K; Martin, K; Morrison, C; Ward, R; Bowden, J; Bowden, G; De Groot, P (2007)
Single crystal 400 nm thick Laves phase [20 Å∈DyFe 2/80 Å∈YFe2]40 superlattice have been grown by MBE with a (110) growth direction. VSM measurements performed at room temperature with an applied field range of ±1.2×105 Oe, directed along the [001] direction, reveal a unique single-phase-liked ferrimagnetic behavior. A dominant exchange spring behavior is revealed by MOKE measurement along the [-110] direction. Furthermore, for striped arrays patterned along the [001] direction with height-to-width ratio of 0.05, a shape anisotropy of the order of 104 erg/cm3 is induced, resulting into a pronounced change of coercivity due to the comparable magnitude with intrinsic anisotropies. The results demonstrate the feasibility of engineering both single-phase-liked and exchange-spring magnet behavior in Laves phase epitaxial hard/soft superlattices by patterning. © Springer-Verlag 2007.